2012
DOI: 10.1177/0145721712458835
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Impact of Cancer Treatment on Diabetes Self-Management

Abstract: Cancer treatment and cancer-related symptoms can have a negative impact on diabetes self-management behaviors in adults with diabetes who are undergoing chemotherapy. Diabetes self-management education is targeted to improve health outcomes in patients with diabetes and cancer and addresses the "cause" not just the "source" of the problem needs to be developed. Further research needs to be done to address issues related to glycemic control and health-related outcomes in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 54 publications
3
59
0
Order By: Relevance
“…As such, this is recognized as a hectic and burdensome time for patients. Prior qualitative work hypothesized that diabetes management becomes sidelined during this acute cancer care phase as the demands of cancer care overwhelm patients . Furthermore, oncologists are subspecialists whose focus is cancer, and the majority view the management of noncancer conditions such as diabetes as beyond their scope .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, this is recognized as a hectic and burdensome time for patients. Prior qualitative work hypothesized that diabetes management becomes sidelined during this acute cancer care phase as the demands of cancer care overwhelm patients . Furthermore, oncologists are subspecialists whose focus is cancer, and the majority view the management of noncancer conditions such as diabetes as beyond their scope .…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid diabetes puts patients with cancer at an increased risk of infections, hospitalizations, and mortality . Insufficient attention to diabetes during active cancer care may explain why diabetic patients with cancer have worse outcomes compared with their nondiabetic cancer counterparts . To our knowledge, few studies to date have documented diabetes management patterns among patients with cancer before and after their cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research reported a higher prevalence of diabetes and suboptimal glycemic control in cancer survivors compared to noncancer survivors, and this varied by cancer types (Stava et al, 2007;Karlin et al, 2012). The reasons for this difference are not clear, but some studies have indicated that cancer treatment such as chemotherapy and cancerrelated symptoms could have a negative impact on diabetes management (Hershey et al, 2012). In addition, many medications used in cancer treatment or organ failure in advanced cancer patients can have an effect on glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…The associated symptoms, such as fatigue, nausea, and loss of appetite, which occur with chemotherapy, are likely to negatively impact an individual's ability to self-manage their diabetes, threatening glycemic control. 26 Individuals with more than 1 chronic illness may prioritize 1 chronic condition over the other, or the symptoms of 1 disorder may impact the actual performance of self-management behaviors required for another disorder. 8,27 Competing demands may develop from symptoms and care requirements associated with cancer and its treatment and impact the actual performance of required self-management activities for diabetes.…”
mentioning
confidence: 99%